PENALARAN MORAL ANAK USIA DINI DALAM BUKU-BUKU DONGENG LITERASI DINI - kasmiati kasmiati (IAIN Purwokerto, 2019)
The results on study of ten literacy fairy tale textbooks for early childhood published by the Language Agency, Ministry of Education and Culture, Republic of Indonesia in 2019 is the first, there are three fairy tale books with moral reasoning oriented to the obedience of punishment which positions the main character of the fairy tale as problematic, and because of this problematic, the main character gets a direct or indirect punishment. Through the punishment received, the main character then realizes his mistake. This fairy tale book builds moral reasoning on early childhood to do good because if they do not do good they will get punishment. Second, five fairytale books with moral reasoning are oriented to the relativist instrument which positions the main character as a person who does good, and because of his good deeds the main character gets a prize. These fairytale books will build moral reasoning in early childhood that every good deed will always get a pleasant gift. Third, two fairy tale books with moral reasoning are oriented to groups of good children who position the main character in a fairy tale who wants to do good because the main goal is to get the recognition of good children whose impact on the acceptance of children in their social groups. These fairytale books build moral reasoning on children that by doing good, then others will call us good children who will be accepted by their friends.